RESORT PANTAI RINDU ALAM DI KABUPATEN TANAH BUMBU DENGAN PENDEKATAN ARSITEKTUR HIJAU - Ashifa Febiana Yunti; Gusti Novi Sarbini; Ira Mentayani (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
Rindu Alam Beach Resort has natural potential that supports the development of a resort design using a green architecture approach. The design produces 5 zones, namely the cottage zone, restaurant, recreation and relaxation, service, and open area. The implementation of green architecture in the short term through the provision of green areas of >35%, environmentally friendly pedestrian paths, the utilization of rainwater and solar panels, the use of local materials, empowerment of local communities in its management, and the use of local architectural building forms such as gable roofs and buildings with a stilt system. While in the long term through waste management and promoting a sustainable lifestyle through information boards and recycled craft products.